Periostin as a predictor of uncontrolled asthma and lung function decrease in patient of different age groups - A. V. Kamaev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2021)
Introduction. Uncontrolled bronchial asthma (BA) increases risk of hospitalizations, future exacerbations and decreases quality of life; factors improving the probability to achieve BA control are under study.Methods and materials. The open prospective study included 104 patients of three groups: children (6—11 years, n=38), adolescents (14—17 years, n = 35) and adults (25 — 50 years, n = 31). Inclusion criteria: BA duration >12 month, uncontrolled asthma, absence of acute respiratory infection for 14 days. Clinical history, respiratory function and sampling (serum and nasal brushings) for periostin assay were performed on Visit 1. Maintenance therapy correction and triggers avoiding recommendations were made. Two further visits 6 months apart were done. Statistical processing included ANOVA (Kruskall — Wallis test) and Pearson correlation test. Differences were considered significant when p<0.05.Results. 75 % of «Children» group,70.6 % of «Adolescents» and 53.6 % of «Adults» had achieved BA control. Obesity, non-atopic phenotype, FEV1 <65 % of predicted were risk factors of uncontrolled BA. Serum periostin levels were highest in uncontrolled BA subgroup, Me [Q25; Q75] =32.9 [28.6; 39.1] ng/ml. Nasal periostin levels were highest in «Adolescent» group: 9.8 [4.8; 11.2] ng/ml. Nasal periostin and low FEV1 had moderate reverse correlation (r=—0.61).Conclusion. Serum and nasal periostin levels could indicate treatment efficacy and prognose future risks of BA control loss.